2008
DOI: 10.1002/elan.200704039
|View full text |Cite
|
Sign up to set email alerts
|

Novel Potentiometric Sensors of Molecular Imprinted Polymers for Specific Binding of Chlormequat

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Sol-gel membranes were obtained by coating a clean graphite support [25] with 200 μL of the viscous ISG solution. This solution was allowed to dry at room temperature.…”
Section: Preparation Of the Membrane Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sol-gel membranes were obtained by coating a clean graphite support [25] with 200 μL of the viscous ISG solution. This solution was allowed to dry at room temperature.…”
Section: Preparation Of the Membrane Electrodesmentioning
confidence: 99%
“…Ion exchangers and neutral macrocyclic compounds have been employed with success for this purpose over the past decades. However, the design of new sensing materials that are complementary to the size and charge of a particular ion may lead to very selective interactions [24][25][26]. This could be done by imprinting the target analyte (SDZ and SMX) on a solid surface [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The general procedure used to prepare the PVC membrane is similar to works reported by Prasada Rao [19,20], Sales [18], Gupta [30], Al Attas [31,32], Ganjali [33] and Shamsipur [34]. Exactly 60 mg PVC was dissolved in 2.5 mL of THF.…”
Section: Electrode Preparationmentioning
confidence: 99%
“…Among the reported researches in the field of electrochemical methods for β -blockers [12][13][14][15], there are only a few papers that concern directly metoprolol [15] and nearly no article is found that reported for detection of metoprolol using MIP based ion-selective electrode. Generally, it can be mentioned that there are only a few reports dealing with potentiometric molecular sensors based on MIPs [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted polymers (MIPs) are a route to obtain such materials and have been introduced successfully in polymeric membranes (Kamel et al, 2008;Moreira et al, 2010). They are specifically designed to display stereochemical interactions with the analyte and act similarly to natural antibodies.…”
Section: Introductionmentioning
confidence: 99%